Intelligent arbitration of DAOs disputes - Lobna Abdalhusen Easa; Jalil Hassan Bashat (Journal of Legal Sciences, 2024)
Smart arbitration in disputes involving Decentralized Autonomous Organizations (DAOs) utilizes blockchain technology and smart contracts to provide efficient solutions for resolving conflicts within the complex digital economy. DAOs, as decentralized entities operating on blockchain protocols, present a new model of governance and contracting that challenges traditional legal frameworks. Given their decentralized and jurisdictionally non-affiliated nature, these organizations encounter difficulties in determining jurisdiction in cases of dispute. However, smart arbitration, relying on automation and transparency provided by smart contracts, can facilitate the swift and effective enforcement of arbitral awards. It offers solutions that transcend the traditional boundaries of the judiciary, allowing arbitration procedures to be executed according to the codes programmed into smart contracts, thereby affording disputing parties access to fair resolutions without the need for traditional litigation. This approach opens new horizons for justice in the digital age and proposes innovative alternatives for addressing contemporary legal challenges.